Carbon material containing molybdenum carbide-molybdenum nitride heterostructure and preparation method and application thereof
By using carbon materials containing molybdenum carbide-molybdenum nitride heterostructure as electrodes, the problem of high energy consumption for hydrogen production by electrolyzing water is solved, and high-efficiency and low-cost electrolyzing water is achieved, which is suitable for large-scale applications.
Patent Information
- Application Number
- CN202411459909.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The energy consumption of hydrogen production by electrolyzing water is high, mainly due to the high energy barrier and slow reaction kinetic rate of the anode oxygen evolution reaction, which leads to the high cost and poor stability of precious metals of electrode materials, which limits the efficiency and large-scale hydrogen production by electrolyzing water. application.
Carbon materials containing molybdenum carbide-molybdenum nitride heterostructure are used as electrode materials, and the catalytic activity and structural stability are improved through the porous carbon matrix and the in-situ growing molybdenum carbide-molybdenum nitride heterostructure layer, thereby reducing energy consumption and Production cost.
This material exhibits excellent catalytic performance, structural stability and mechanical strength in electrolyzing hydrogen production, effectively reducing energy consumption and improving efficiency, and has low production costs and wide sources of raw materials, making it suitable for large-scale industrial production.
Smart Images

Figure CN119243243A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure, and a preparation method and application thereof. Background Art
[0002] Hydrogen has the advantages of light weight, high energy density, high calorific value, and pollution-free combustion, and is considered one of the most promising energy sources. However, hydrogen energy is not an energy resource that exists in large quantities in nature, but needs to be produced artificially. Among the many hydrogen production methods, hydrogen production by water electrolysis has the advantages of simple preparation process, clean and pollution-free, and relatively mature technology. It is currently recognized as the hydrogen production method with the best application prospects.
[0003] The OWS reaction consists of two half reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). The HER reaction involves a two-electron transfer process, while the OER reaction involves a four-electron transfer process. 3 H2~5.5kWh / Nm 3 H2), the main reason is that the energy barrier of OER reaction is high and the reaction kinetics rate is slow, which seriously affects the efficiency of hydrogen production by water electrolysis. Studies have shown that the use of high-efficiency catalytic electrode materials to reduce the reaction activation energy can effectively reduce the energy consumption of hydrogen production by water electrolysis. Therefore, in the production of hydrogen by water electrolysis, it is crucial to improve the activity of electrode catalytic materials, reduce the overpotential of oxygen evolution reaction, and improve the stability of electrode materials. At present, commercial electrode materials are mainly precious metal materials (for example: platinum-based materials for HER reactions, ruthenium / iridium-based materials for OER reactions). Although they have excellent catalytic properties, the reserves of precious metal elements such as platinum, ruthenium, and iridium on the earth are very limited, the price fluctuates greatly, the production cost is high, and these precious metal materials have poor long-term stability at high potentials, which seriously limits their large-scale application in the field of hydrogen production by water electrolysis.
[0004] Therefore, it is of great significance to develop an electrode material with excellent catalytic performance, good stability, low production cost and wide source of raw materials. Summary of the invention
[0005] The object of the present invention is to provide a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure comprises a porous carbon matrix and a molybdenum carbide-molybdenum nitride heterostructure layer in-situ grown on the surface of the porous carbon matrix; the molybdenum carbide-molybdenum nitride heterostructure layer comprises molybdenum carbide and molybdenum nitride.
[0008] A method for preparing the carbon material containing molybdenum carbide-molybdenum nitride heterostructure as described above comprises the following steps:
[0009] 1) Slice the wood transversely and then place it in a protective atmosphere for carbonization to obtain porous carbon;
[0010] 2) placing the porous carbon as a working electrode in an electrolyte containing a molybdenum source for electrodeposition to obtain a porous carbon with molybdenum oxide in situ grown on the surface;
[0011] 3) The porous carbon with molybdenum oxide in situ grown on the surface and melamine are placed in a protective atmosphere and heated to react, so as to obtain a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure.
[0012] Preferably, the wood in step 1) is at least one of shrubs and trees.
[0013] Further preferably, the wood in step 1) is poplar.
[0014] Preferably, the protective atmosphere in step 1) is a nitrogen atmosphere or an argon atmosphere.
[0015] Preferably, the carbonization in step 1) is carried out at a temperature of 300° C. to 1000° C., and the carbonization time is 1 h to 15 h.
[0016] Preferably, the molybdenum source in the electrolyte containing a molybdenum source in step 2) is a molybdenum salt.
[0017] Further preferably, the molybdenum source in the molybdenum source-containing electrolyte in step 2) is at least one of ammonium heptamolybdate, sodium molybdate, and molybdenum pentachloride.
[0018] Preferably, the concentration of the molybdenum source in the electrolyte containing the molybdenum source in step 2) is 0.001 mol / L to 3 mol / L.
[0019] Preferably, the solvent in the electrolyte containing the molybdenum source in step 2) is at least one of water, ethanol, ethanolamine, diethanolamine, triethanolamine, N,N-dimethylformamide, and ethylenediamine.
[0020] Preferably, the electrodeposition in step 2) is carried out at a deposition potential of 0 V to -2.0 V (relative to a reference electrode), and the electrodeposition time is 0.1 h to 10 h.
[0021] Preferably, the protective atmosphere in step 3) is a nitrogen atmosphere or an argon atmosphere.
[0022] Preferably, the reaction in step 3) is carried out at a temperature of 200° C. to 1000° C., and the reaction time is 0.5 h to 5 h.
[0023] An application of the carbon material containing the molybdenum carbide-molybdenum nitride heterostructure as described above in hydrogen production by water electrolysis.
[0024] The beneficial effects of the present invention are as follows: the carbon material containing the molybdenum carbide-molybdenum nitride heterostructure of the present invention has the advantages of excellent catalytic performance, good structural stability, high mechanical strength, etc. when used as an electrode material for hydrogen production by electrolysis of water. It can effectively reduce the energy consumption of hydrogen production by electrolysis of water and improve the efficiency of hydrogen production by electrolysis of water. In addition, it has low production cost, wide source of raw materials, and simple preparation method, and is suitable for large-scale industrial production and application.
[0025] Specifically:
[0026] 1) The carbon material containing molybdenum carbide-molybdenum nitride heterostructure of the present invention comprises a porous carbon matrix and a molybdenum carbide-molybdenum nitride heterostructure layer in situ grown on the surface of the porous carbon matrix. The porous carbon matrix has good conductivity and high specific surface area, and can provide abundant reaction active sites and electron transmission channels, while the molybdenum carbide-molybdenum nitride heterostructure can improve the activity of the active sites and expose more active sites, thereby improving the electrocatalytic activity. In addition, the performance of the molybdenum carbide-molybdenum nitride heterostructure can be adjusted and optimized by controlling the concentration of the molybdenum source in the electrolyte, the deposition potential and the deposition time, and the amount of melamine, and has good repeatability;
[0027] 2) The carbon material containing molybdenum carbide-molybdenum nitride heterostructure of the present invention has a three-dimensional hierarchical porous structure, low-curvature microchannels, adjustable hydrophilicity / hydrophobicity and good mechanical properties, a large electrochemical active area, high intrinsic electrochemical activity, regulated electronic structure, and reduced water dissociation energy barrier. It can construct an efficient gas-liquid-solid three-phase reaction interface for electrolysis of water, and the use of wood charcoal as a substrate is conducive to further reducing the cost of large-scale production;
[0028] 3) The carbon material containing molybdenum carbide-molybdenum nitride heterostructure of the present invention has good structural stability and high mechanical strength, can effectively resist volume expansion and structural damage, and exhibits excellent water electrolysis performance and stability;
[0029] 4) The carbon material containing molybdenum carbide-molybdenum nitride heterostructure of the present invention has low production cost, wide raw material source, simple preparation method, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart for preparing the carbon material containing molybdenum carbide-molybdenum nitride heterostructure.
[0031] Figure 2 This is the XRD pattern of Mo2N / Mo2C@CW in Example 1.
[0032] Figure 3 These are the SEM images, TEM images, SAED images and EDS energy spectrum images of Mo2N / Mo2C@CW in Example 1.
[0033] Figure 4 HER performance diagram of the carbon material containing molybdenum carbide-molybdenum nitride heterostructure in Examples 1 to 5.
[0034] Figure 5 This is the Tafel slope diagram of Mo2N / Mo2C@CW in Example 1.
[0035] Figure 6 Nengquist diagram of CW and Mo2N / Mo2C@CW in Example 1.
[0036] Figure 7 This is the electrochemical activity area diagram of Mo2N / Mo2C@CW in Example 1.
[0037] Figure 8 This is the water contact angle test results of CW and Mo2N / Mo2C@CW in Example 1. DETAILED DESCRIPTION
[0038] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0039] Embodiment 1:
[0040] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure, the preparation method of which is as follows (the preparation flow chart is as follows Figure 1 shown):
[0041] 1) Poplar wood was sliced transversely (perpendicular to the growth direction) into wood chips with a size of 4 cm × 2 cm × 0.1 cm, then washed with water and dried overnight at 80 ° C in a forced air drying oven, then placed in a quartz tube furnace, nitrogen was passed through, and the temperature was increased from room temperature to 500 ° C at a heating rate of 5 ° C / min, and kept at this temperature for 1.5 h, and then continued to be heated to 900 ° C at a heating rate of 5 ° C / min, and kept at this temperature for 1 h, to obtain porous carbon (denoted as CW);
[0042] 2) 1 mmol of (NH4)6Mo7O 244H2O was added to 60mL of deionized water, stirred and dissolved to prepare a molybdenum salt solution, and then a three-electrode system was assembled using porous carbon as a working electrode (WE), Hg / HgO electrode as a reference electrode (CE), a carbon rod electrode as a counter electrode (RE), and a molybdenum salt solution as an electrolyte. Then, a power supply was applied to deposit at a potential of -0.9V (relative to the Hg / HgO electrode) for 30min, and then the porous carbon was taken out and washed with deionized water several times, and then placed in a forced air drying oven at 60°C for 12h to obtain a porous carbon with molybdenum oxide in situ grown on the surface (denoted as Mo2O3@CW);
[0043] 3) The porous carbon with molybdenum oxide in situ grown on the surface is placed in a quartz tube furnace, and 0.5 g of melamine is placed upstream of the quartz tube furnace, and nitrogen is introduced. The temperature is then increased from room temperature to 500°C at a heating rate of 5°C / min, and kept warm for 1 hour. The temperature is then continued to be increased to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure (denoted as Mo2N / Mo2C@CW).
[0044] Performance Testing:
[0045] 1) The X-ray diffraction (XRD) pattern of the carbon material containing molybdenum carbide-molybdenum nitride heterostructure (Mo2N / Mo2C@CW) in this embodiment is as follows Figure 2 shown.
[0046] Depend on Figure 2 It can be seen that the characteristic peaks at 37.4° and 63.1° are attributed to the diffraction peaks of the (111) and (220) crystal planes of Mo2N, respectively, while the characteristic peaks at 34.3° and 39.3° are attributed to the diffraction peaks of the (021) and (121) crystal planes of Mo2C, respectively, indicating that Mo2N / Mo2C@CW does contain Mo2C-Mo2N heterostructure.
[0047] 2) The scanning electron microscope (SEM) image, transmission electron microscope (TEM) image, selected area electron diffraction (SAED) image and EDS energy spectrum image of the carbon material (Mo2N / Mo2C@CW) containing molybdenum carbide-molybdenum nitride heterostructure in this embodiment are as follows: Figure 3 (a, b and c are SEM images, d is a TEM image, e is a SAED image, and f, g, h and i are EDS energy spectra).
[0048] Depend on Figure 3 From a, b and c in Fig. 1, it can be seen that the Mo2N-Mo2C heterostructure grows uniformly in the vertical channels of the porous carbon (CW);
[0049] Depend on Figure 3 From the d in Mo2N / Mo2C@CW, we can know that and The lattice spacings belong to the (121) and (021) planes of Mo2C, respectively. The lattice spacing belongs to the (111) crystal plane of Mo2N;
[0050] Depend on Figure 3 From Figure e, we can see that the selected electron diffraction pattern of Mo2N / Mo2C@CW clearly shows the (021) crystal plane of Mo2C and the (111) crystal plane of Mo2N;
[0051] Depend on Figure 3 From images f, g, h and i, we can see that the C, N and Mo elements in Mo2N / Mo2C@CW are evenly distributed, indicating the successful introduction and uniform distribution of the Mo2N-Mo2C heterostructure.
[0052] Embodiment 2:
[0053] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure (denoted as Mo2N / Mo2C@CW-0.8V) is exactly the same as Example 1 except that the electrodeposition potential in step 2) is adjusted from "-0.9V" to "-0.8V" during preparation.
[0054] Embodiment 3:
[0055] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure (denoted as Mo2N / Mo2C@CW-1.0V) is exactly the same as Example 1 except that the electrodeposition potential in step 2) is adjusted from "-0.9V" to "-1.0V" during preparation.
[0056] Embodiment 4:
[0057] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure (denoted as Mo2N / Mo2C@CW-0.4g) is exactly the same as Example 1 except that the amount of melamine in step 3) is adjusted from "0.5g" to "0.4g" during preparation.
[0058] Embodiment 5:
[0059] A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure (denoted as Mo2N / Mo2C@CW-0.6g) is exactly the same as Example 1 except that the amount of melamine in step 3) is adjusted from "0.5g" to "0.6g" during preparation.
[0060] Performance Testing:
[0061] 1) HER performance of the carbon material containing molybdenum carbide-molybdenum nitride heterostructure in Examples 1 to 5 (HER performance test process is as follows: the carbon material containing molybdenum carbide-molybdenum nitride heterostructure in Examples 1 to 5 is used as the working electrode, the Hg / HgO electrode is used as the reference electrode, the carbon rod electrode is used as the counter electrode, and the KOH solution with a concentration of 1 mol / L is used as the electrolyte to assemble a three-electrode electrochemical cell, and then the test is performed using a CHI660E electrochemical workstation) as shown in the figure Figure 4 (The commercial Pt / C electrode is used as a comparison, denoted as Pt / C@CW).
[0062] Depend on Figure 4 As shown in a, the Mo2N / Mo2C@CW in Example 1 only needs an ultra-low overpotential of 193 mV to obtain 100 mA cm -2 The current density is better than that of Mo2N / Mo2C@CW-0.8V(η 100 =234mV), Mo2N / Mo2C@CW-1.0V(η 100 =324mV) and commercial Pt / C electrode (η 100 =267mV);
[0063] Depend on Figure 4 As shown in Figure 2, the Mo2N / Mo2C@CW in Example 1 only needs an ultra-low overpotential of 193 mV to obtain 100 mA cm -2 The current density is better than that of Mo2N / Mo2C@CW-0.4g(η 100 =291mV) and Mo2N / Mo2C@CW-0.6g(η 100 =248mV).
[0064] 2) The Tafel slope of the carbon material containing molybdenum carbide-molybdenum nitride heterostructure (Mo2N / Mo2C@CW) in Example 1 is as follows: Figure 5 (Commercial Pt / C catalyst was used as a comparison, denoted as Pt / C).
[0065] Depend on Figure 5 It can be seen that Mo2N / Mo2C@CW exhibits 96mV·dec -1 The Tafel slope is slightly lower than that of commercial Pt / C catalyst (161 mV·dec -1 ).
[0066] 3) The Nengquist plots of the porous carbon (denoted as CW) and the carbon material containing molybdenum carbide-molybdenum nitride heterostructure (Mo2N / Mo2C@CW) in Example 1 are shown in FIG. Figure 6 shown.
[0067] Depend on Figure 6 It can be seen that Mo2N / Mo2C@CW has extremely low impedance.
[0068] 4) Electrochemical activity area diagram of the carbon material (Mo2N / Mo2C@CW) containing molybdenum carbide-molybdenum nitride heterostructure in Example 1 (the test process is as follows: a CHI660E electrochemical workstation is used to perform cyclic voltammetry scanning at different scan rates within a selected voltage range, and the obtained curve is as follows Figure 7 a in, from Figure 7 Select a certain voltage in a, and calculate the corresponding two currents to obtain the electrochemical active surface area. Figure 7 b) as in Figure 7 shown.
[0069] Depend on Figure 7 It can be seen that Mo2N / Mo2C@CW exhibits a higher double-layer capacitance (C dl =38.51mF·cm -2 ), corresponding to a higher electrochemically active area.
[0070] 5) The water contact angle test results of the porous carbon (denoted as CW) in Example 1 and the carbon material containing molybdenum carbide-molybdenum nitride heterostructure (Mo2N / Mo2C@CW) are shown in the figure below: Figure 8 shown.
[0071] Depend on Figure 8 It can be seen that CW exhibits a water contact angle of 120°, while Mo2N / Mo2C@CW exhibits a hydrophilic angle of 0° to water, indicating that Mo2N / Mo2C@CW has excellent hydrophilicity.
[0072] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A carbon material containing a molybdenum carbide-molybdenum nitride heterostructure, characterized in that: The composition includes a porous carbon matrix and a molybdenum carbide-molybdenum nitride heterostructure layer in-situ grown on the surface of the porous carbon matrix; the composition of the molybdenum carbide-molybdenum nitride heterostructure layer includes molybdenum carbide and molybdenum nitride.
2. A method for preparing a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure as claimed in claim 1, characterized in that: The following steps are involved: 1) Slice the wood transversely and then place it in a protective atmosphere for carbonization to obtain porous carbon; 2) placing the porous carbon as a working electrode in an electrolyte containing a molybdenum source for electrodeposition to obtain a porous carbon with molybdenum oxide in situ grown on the surface; 3) The porous carbon with molybdenum oxide in situ grown on the surface and melamine are placed in a protective atmosphere and heated to react, so as to obtain a carbon material containing a molybdenum carbide-molybdenum nitride heterostructure.
3. The preparation method according to claim 2, characterized in that: Step 1) The wood is at least one of a shrub or a tree.
4. The preparation method according to claim 2 or 3, characterized in that: Step 1) The carbonization is carried out at a temperature of 300° C. to 1000° C. and the carbonization time is 1 h to 15 h.
5. The preparation method according to claim 2, characterized in that: Step 2) The molybdenum source in the electrolyte containing a molybdenum source is a molybdenum salt.
6. The preparation method according to claim 2 or 5, characterized in that: Step 2) The concentration of the molybdenum source in the electrolyte containing the molybdenum source is 0.001 mol / L to 3 mol / L.
7. The preparation method according to claim 2 or 5, characterized in that: Step 2) The solvent in the electrolyte containing the molybdenum source is at least one of water, ethanol, ethanolamine, diethanolamine, triethanolamine, N,N-dimethylformamide, and ethylenediamine.
8. The preparation method according to claim 2 or 5, characterized in that: Step 2) The electrodeposition is carried out at a deposition potential of 0 V to -2.0 V, and the electrodeposition time is 0.1 h to 10 h.
9. The preparation method according to any one of claims 2, 3 and 5, characterized in that: Step 3) The reaction is carried out at a temperature of 200°C to 1000°C and a reaction time of 0.5h to 5h.
10. Use of the carbon material containing molybdenum carbide-molybdenum nitride heterostructure as claimed in claim 1 in hydrogen production by water electrolysis.
Citation Information
Patent Citations
Preparation method and application of nano composite film
CN113584552A
Biomass carbon-based nano molybdenum carbide-molybdenum nitride heterojunction composite catalyst and method
CN114214640A
Self-supporting integrated electrode material derived from wood charcoal as well as preparation method and application of self-supporting integrated electrode material
CN117328084A
